Ion selective separators based on graphene oxide for stabilizing lithium organic batteries. Issue 8 (15th June 2018) - Pan, Yuede; Hao, Junran; Zhu, Xuanbo; Zhou, Yahong; Chou, Shu-Lei
Abstract : A thin bicomponent layer with GO and Super P enhances electroactive cathode material utilization for stable lithium organic batteries. Abstract : Ion selective membranes exist widely in the biological world and have been mimicked by scientists and engineers for the purpose of manipulating ion flow. For instance, polymers with sulfonate groups like Nafion are applied in proton exchange membrane fuel cells for facilitating proton transport whilst blocking other species. Herein, ion selective separators composed of graphene oxide (GO) and Super P (or graphene) are applied for stabilizing lithium organic batteries. The reconstructed GO sheets form numerous negatively charged nanochannels, which selectively allow the transport of lithium ions and reject the electroactive organic anions. Meanwhile, Super P (or graphene) on top of the coating layer functions as the upper current collector for reactivating the electroactive organic species. In this work, two typical carbonyl electrode materials with, respectively, two (anthraquinone, AQ) and four (perylene-3, 4, 9, 10-tetracarboxylic dianhydride, PTCDA) carbonyl groups are applied as examples. Compared to the pristine Celgard separator, the ion selective separators enable significantly alleviated self-discharge, improved coulombic efficiency and cycling stability.